THE ADMINISTRATION OF SOCIAL SECURITY IN THE MIDST OF COVID-19: A NEED FOR A SPECIALISED AND INDEPENDENT SOCIAL SECURITY ADJUDICATION SYSTEM IN SOUTH AFRICA - Ntando Ncamane (Obiter, 2023)
The spread of the Coronavirus has had an adverse effect in many parts of the world including South Africa. Many people contracted the disease, and some even died. It is worth mentioning that to date, people are still contracting and dying from this disease. Related consequences that came with the management of the disease have had dire repercussions both on the economy of the country and social conditions of many, in particular the impoverished. In a bid to circumvent the socio-economic hardships given birth to by the disease the State made provision for a number of social relief measures to improve the conditions of those who were at the plight of poverty. These social relief measures had their own shortcomings, such as mismanagement of allocated funds, fraud and maladministration. These shortcomings left the intended beneficiaries destitute. At this point those affected by such discrepancies had no recourse available to them due to lack of awareness, lengthy adjudication processes, exorbitant legal fees and most importantly the lack of an independent social security adjudication system to solely deal with matters of this nature. The lack of an independent social security adjudication system invites quite a number of constitutional breaches such as the breach of the right to social security and the right of access to courts and in turn, has a bearing on socio-economic rights during this era of the pandemic. In an endeavour to provide amicable solutions to the above shortcomings, this article suggests that the pandemic necessitated the implementation of the long-called-for establishment of an independent social security adjudication system which will only deal with social-security-related matters. To amplify the need for an independent social security adjudication system the article makes recommendations to this effect. It is worth mentioning that the article was written at the height of Covid-19 and when the lockdown regulations were still in force and effective, this is thus reflective in the contents of the article.